PENGARUH NILAI HEDONIC DAN NILAI UTILITARIAN TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO EMAS GADJAH DI KOTA PASURUAN - Mutmainnah, Mutmainnah; Hastari, Sri; Woro Subagio, Dyajeng Puteri (Yayasan Education and Social Center, 2024)
The rapid development and competition in the field of trade, demands various innovations in marketing products. Gold jewelry is an object that is used to make up or beautify yourself and cannot be separated from women. Wrong One jewelry shop in Pasuruan is Gadjah Gold Shop. This research aims to determine the influence of hedonic value and Utilitarian value of purchasing decisions at the Gadjah Gold Shop in Pasuruan. The population used is previous consumers make purchases at the Gadjah Gold Shop in Pasuruan City with a sampling method, namely accidental sampling. Use Hair et al.'s formula, with a sample size of 70 respondents. The analysis used is Instrument Test, Description Analysis, Test Classical Assumptions, Multiple Linear Regression Analysis, Coefficient Analysis Determination and Hypothesis Testing. The research results show that 1) The influence of hedonic value and utilitarian value simultaneously influences positive and significant on purchasing decisions at the Gold Shop Gadjah in Pasuruan City with a value of Fcount > Ftable, namely 248.722>3.13 and the sig value. 0.000<0.05. 2) Hedonic value partial has a positive and significant effect on decisions purchases at the Gadjah Gold Shop in Pasuruan City with value tcount > ttable, namely 22.254>1.996 and the sig.0.000<0.05. 3) Value partial utilitarianism does not have a positive and significant effect on purchasing decisions at the Gadjah Gold Shop in Kota Pasuruan with a value of tcount> ttable, namely 0.956>1.996 and value sig.0.000<0.05